Nep-hop for peace? Political visions and divisions in the booming Nepalese hip-hop scene. (May 2021) - Lundqvist, Martin
This article explores the burgeoning Nepalese hip-hop scene – commonly known as nep-hop – as a discursive intervention in the post-war politics of Nepal. Its core argument is that nep-hop oftentimes demonstrates an ethos of peacebuilding through popular culture. Indeed, many songs explicitly criticize violence, war, and the political leaders who recently brought the nation to a civil war. Yet, this political critique appears to often fall on deaf ears, due to the fact that nep-hop is commonly decoded as a radically 'alien' and 'vulgar' genre by audiences in mainstream Nepalese society. Importantly, however, this should not be read as a rejection of the ideological content of nep-hop, but rather as a negative evaluation of the aesthetic form of the genre, which bars many Nepalese citizens from engaging with its political messages in a meaningful manner.